Taxonomy and feeding of Forcipomyia (Microhelea) fuliginosa Meigen and Forcipomyia (Microhelea) esakiana Tokunaga (Diptera: Ceratopogonidae) on Antheraea mylitta Drury (Lepidoptera: Saturniidae) - Mazumdar, Shuddhasattwa Maitra; Banerjee, Nabanita; Reddy, Bommireddy Thirupam; Kar, Surajit; Sathyanarayana, Kutala; Mazumdar, Abhijit (Zootaxa, 2024)
Taxonomic equivocality and complexity exist in the two species of Ceratopogonids, Forcipomyia (Microhelea) fuliginosa Meigen and Forcipomyia (Microhelea) esakiana Tokunaga. Incongruencies and inaccuracies in species identification restrict further biological and ecological studies on the host-ectoparasite association. Preferential landing and hemolymphophagy of F. fuliginosa and F. esakiana on Antheraea mylitta Drury larva were studied under field conditions. The silkworm A. mylitta is reared in the tasar sericulture industry, contributing 1466 metric tons (2021–22) of indigenous raw silk in India. Ectoparasitic behavior of the biting midges, F. fuliginosa, and F. esakiana is an increasing threat to the silkworm, necessitating proper identification. Intra and inter-variations of these two closely related species have been stated. Morphological-based identification of these species has been substantiated with COX1 molecular data. A Bayesian-modeled approach to reconstruct the dendrogram of the two species based on the COX1 sequences generated has been presented along with the referred sequences of F. fuliginosa from Genebank. The species F. esakiana is being reported for the first time from India, along with its ectoparasitic hemolymphophagous nature. The role of these insectivorous species in transmitting pathogens to the larvae of tasar silk needs further investigation.